What Makes Biology Unique? : Considerations on the Autonomy of a Scientific Discipline. - Mayr, Ernst (Cambridge University Press, 2004)
This book is a collection of revised and new essays from the most eminent evolutionary biologist of the past century, written in time for his 100th birthday. Here Ernst Mayr explores biology as an autonomous science, the history of evolutionary thought, the contributions of philosophy to the science of biology, and the major ongoing issues in evolutionary theory.